Perancangan Ulang Tata Letak Fasilitas Pabrik Menggunakan Metode Blocplan “CV. Tempe Suryadi Sentosa” - Ramadhan, Yahya; Chandra, Ahmad Farozi Eka; Rini, Asih Setyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
CV. Tempe Suryadi Sentosa is a company engaged in the manufacture of tempeh, a traditional food of Tangerang, which is spread across almost all areas of Tangerang, namely Tangerang City, Tangerang Regency, South Tangerang City, and parts of Serang. Therefore, the company's Operational Research at CV. Tempe Suryadi Sentosa must be carried out smoothly, and its layout must not be frequently obstructed. Various facilities and spaces must be in accordance with the various activities carried out to ensure that the process runs smoothly and worker comfort is maintained. In this study, the identification of relationships between facilities was carried out using the Activity Relationship Chart (ARC). Each facility is categorized into work stations. After determining the relationships between facilities, the next step is to design the facility layout using the BLOCPLAN method, which produces five alternative proposed facility layouts. The results of the facility layout design research using the BLOCPLAN method Each alternative facility layout has an Adjacency Score, R-Score, and Rel-dist Score which will be used as criteria for selecting the best alternative facility layout. And the latest layout is 13 with a layout score of 0.5